2011
DOI: 10.1042/bj20102167
|View full text |Cite
|
Sign up to set email alerts
|

Group IVA phospholipase A2 regulates testosterone biosynthesis by murine Leydig cells and is required for timely sexual maturation

Abstract: In the present paper, we report that PLA2G4A (Group IVA phospholipase A2) is important in the development and function of rodent testes. Interstitial cells of rat testes had high PLA2 (phospholipase A2) activity that was very sensitive to the PLA2G4A-preferential inhibitor AACOCF3 (arachidonyl trifluoromethyl ketone). PLA2G4A protein was expressed primarily in the interstitial cells of wild-type mouse testes throughout maturation. Although Pla2g4a knockout (Pla2g4a−/− ) male mice are fertile, their sexual matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Another two genes that are worth noting due to their participation in testis development are PLA2G4A (Kurusu et al . ), which also is linked to the ovulation process (Diouf et al . ) and speculatively to prostaglandin F2a reproductive pathways (Ababneh & Troedsson ), and OVOL1, which interacts with ID2 , both regulators of spermatogenesis (Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…Another two genes that are worth noting due to their participation in testis development are PLA2G4A (Kurusu et al . ), which also is linked to the ovulation process (Diouf et al . ) and speculatively to prostaglandin F2a reproductive pathways (Ababneh & Troedsson ), and OVOL1, which interacts with ID2 , both regulators of spermatogenesis (Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6J mice used in the present study were generated previously by gene targeting to disrupt an exon of the Pla2g4a gene that resulted in creation of a null allele (21, 32). Heterozygotes were interbred to produce homozygous null and wild‐type littermate mice.…”
Section: Methodsmentioning
confidence: 99%
“…In the superovulation model, adult female mice received a single dose of equine chorionic gonadotropin (eCG; 0.2 IU/g of body weight, intraperitoneally; Sigma Chemical Co., St. Louis, MO, USA) and 48 h later, were injected with human CG (hCG; 5 IU/mouse, intraperitoneally; Sigma). Female mice were housed overnight with a fertile male of various Pla2g4a genotypes (21, 32), and mating was confirmed by the presence of a vaginal plug the next morning [day 1 of pregnancy (PRG1)]. Between 9:00 and 11:00 AM on day 2 of pregnancy (PRG2) we sampled blood by cardiac puncture and sacrificed the mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more detailed study showed that cPLA 2 ␣ modestly regulates ovulation and fertilization by promoting the induction of COX-2 for PG production ( 153 ). A role for cPLA 2 ␣ in regulating male sexual maturation has also been described ( 154 ). Male cPLA 2 ␣ KO mice are fertile but exhibit abnormal histology of the testes showing a reduced number of interstitial cells.…”
Section: Livermentioning
confidence: 99%